Why is Ferrocene so Exceptional? - Astruc, Didier (European journal of inorganic chemistry, 2017)
The appearance of ferrocene in the middle of the 20th century has revolutionized organometallic chemistry and is now providing applications in areas as varied and sometimes initially unexpected as optical and redox devices, battery and other materials, sensing, catalysis, including asymmetric and enantioselective catalysis, and medicine. The author presents here a general, although personal, view of ferrocene's chemistry, properties, functions, and applications through a literature survey involving both historical and up‐to‐date trends and including examples of his group's research in a number of these areas. The review gathers together general features of ferrocene chemistry and representative examples of the salient aspects. Its focus is on ferrocene's basic properties, ferrocene‐containing ligands, the ferrocene/ferricinium redox couple, ferrocene mixed‐valence and average‐valence systems, the ferricinium/ferrocene redox shuttle in catalysis, ligand‐exchange reactions, ferrocene‐containing polymers, ferrocene‐containing structures for cathodic battery and other materials, ferrocenes in supramolecular ensembles, liquid crystals, and nonlinear optical materials, ferrocene‐containing stars and their electrostatic effects, ferrocene‐containing dendrons, dendrimers, and nanoparticles (NPs) and their application in redox sensing and catalysis, and ferrocenes in nanomedicine. The most remarkable properties of ferrocene and its structure and chemistry are emphasized, from historical aspects to recent trends, in an overview justifying why it is such an exceptional tool in asymmetric catalysis, electron‐transfer processes, sensing, molecular engineering, opto‐electronics, materials science and medicine.